Solidarity as Acknowledged Dependence - Schwarz, Philip (Eurostudia, 2020)
In the light of a virtue-ethical turn in the ethics of public health, I discuss the call for solidarity in the pandemic. I develop a reading of Alasdair MacIntyre’s concept of Acknowledged Dependence to provide a basis for a virtue-ethical account of solidarity. Virtues enable correct responses to characteristic experiences of a human life. Solidarity and compassion correspond to the experience of mutual dependence in a way that is conducive to the common good. Compliance with precautions against the pandemic can be understood as exercises of uncalculating giving in the context of a community in which everyone owes this uncalculating giving to everyone else and, in this sense, acts of solidarity.